Draft Annual Plan 1987-88 Volume : V General Areas Government of Assam - Planning Commission (Planning Commission, 1987)
Last but not the-least, the Pre-primary early childhood Education (including Chile care) which is one of the major emphasis of NPE, and also a most important pre-requisite and feeder support for primary education must be stressed upon by opening pre-primary Classes in every primary schools of the state. The same school building will be used by improving. The minimum standard 'with furniture's equipment's etc. for Pre-primary classes also.
Government of Assam, Planning and Development Department